Exchange Depreciation and International Monetary Stability - Polak, J. J. (The Review of Economics and Statistics, 1947)
UNDER the new statute, the Bretton Woods Agreement, which defines obligations of countries regarding international financial policies, exchange depreciation has been accepted as the correct and suitable policy to correct a 2 There is no agreed definition as to what constitutes a fundamental disequilibrium.3 But it would seem without question that the definition comprises a position of disequilibrium in the balance of payments of a country lasting over a certain period of time and resulting in a persistent decrease of that country's liquid assets.4 object of the present paper is to draw attention to the existence of two different types of each of which has the following characteristics: (a) it will lead to a persistent balance of payments deficit, and (b) for the country concerned, this deficit can be eliminated by an alteration of the rate of exchange. But while for one of these two types of disequilibrium the alteration of the rate of exchange of one country has an equilibrating effect on the economies of all countries, such an alteration creates serious new disequilibria if the original disequilibrium is of the other type. main part of this paper will be devoted to an analysis of the international effects of exchange adjustment in this second case. Failure to make adequate distinction between these two types of disequilibrium may have been caused by a lack of adequate terminology and by the consequent over-extensive reliance on the terms and undervaluation. Overvaluation is being used to describe two different things. In the first place it refers to a cause of a balance of payments disequilibrium, namely a relative rise in prices in a country (after allowing for changes in the rate of exchange) compared with the world. It is in this sense that one would state that the I945 rate of 50 French francs to the dollar constituted an overvaluation of the franc. In the second place the term indicates the existence of a balance of payments disequilibrium, without reference to any particular cause. In this sense it was said that sterling was overvalued in I945 and I946, although the point was made at the same time that comparing relative prices or relative price increases in the United Kingdom and the United States, sterling was undervalued compared with the dollar. Since a country's balance of payments depends not only on relative prices, these two situations may, but need not at all, coincide. It would seem to contribute to clarity on 1The author is an official of the International Monetary Fund. This paper was written prior to his employment by the Fund and should not be considered as an expression of the views of that organization. 2 Articles of Agreement of the International Monetary Fund, Article IV, Section 5. Recent experience shows interesting cases of appreciation to correct a favorable disequilibrium (Canada, Sweden). This paper deals with the unfavorable type of disequilibrium only. 'For a discussion of the difficulties of defining this term, see Ragnar Nurske, Conditions of International Monetary Equilibrium, Essays on International Finance, No. 4, Princeton, N. J. 'A recent interpretation of the Articles of Agreement of the Fund, recognizing in principle chronic unemployment as a legitimate cause for depreciation, does not go far toward providing a general definition of the term interpretation made by the Executive Directors of the Fund on September 26, I946, was as follows: The Government of the United Kingdom has stated its intention to maintain full employment and has requested an interpretation of the Articles of Agreement as to whether steps necessary to protect a member from unemployment of a chronic or persistent character, arising from pressure on its balance of payments, shall be measures necessary to correct a fundamental disequilibrium. The Executive Directors interpret the Articles of Agreement to mean that steps which are necessary to protect a member from unemployment of a chronic or persistent character, arising from pressure on its balance of payments, are among the measures necessary to correct a fundamental disequilibrium; and that in each instance in which a member proposes a change in the par value of its currency to correct a fundamental disequilibrium the Fund will be required to determine, in the light of all relevant circumstances, whether in its opinion the proposed change is necessary to correct the fundamental